Development of tetracycline-modified nanoparticles for bone-targeted delivery of anti-tubercular drug - Liang, Qiuzhen; Zhang, Pengfei; Zhang, Liang; Luan, Haopeng; Li, Xinxia; Xiang, Haibin; Jing, Shuang; Song, Xinghua (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Since the poor response to existing anti-tuberculosis drugs and low drug concentration in local bone tissues, the traditional drug therapy does not result in satisfactory treatment of osteoarticular tuberculosis. Thus, we report a rifapentine release system with imparted bone targeting potential using tetracycline (TC) -modified nanoparticles (NPs).Methods: TC was conjugated to PLGA-PEG copolymer via a DCC/NHS technique.Rifapentine-loaded NPs were prepared by premix membrane emulsification technique.The resulting NPs were characterized in terms of physicochemical characterization, hemolytic study, cytotoxicity, bone mineral binding ability, in vitro drug release, stability test and antitubercular activity. The pharmacokinetic and biodistribution studies were also performed in mice.Results: Rifapentine loaded TC-PLGA-PEG NPs were proved to be 48.8 nm in size with encapsulation efficiency and drug loading of 83.3 ± 5.5 % and 8.1 ± 0.4 %, respectively. The release of rifapentine from NPs could be maintained for more than 60 h. Most (68.0%) TC-PLGA-PEG NPs could bind to HAp powder in vitro. The cellular studies revealed that NPs were safe for intravenous administration. In vivo evaluations also revealed that the drug concentration of bone tissue in TC-PLGA-PEG group was significantly higher than that in other groups at all time (P ＜ 0.05). Both NPs could improve pharmacokinetic parameters without evident organ toxicity. The minimal inhibitory concentration of NPs was 0.094 μg/mL, whereas this of free rifapentine was 0.25 μg/mL.Rifapentine loaded TC-PLGA-PEG NPs could increase the amount of rifapentine in bone tissue, prolong drug release in systemic circulation, enhance anti-tuberculosis activity, and thereby reducing dose and frequency of drug therapy for osteoarticular tuberculosis.